An inside story of a thrombosed pile - Yashwant Kumar; Alka Bhatia (Clinics and Practice, 2011)
We report a case of extremely rare variant of ano-rectum malignant tumor. The tumor is often misdiagnosed as either hemorrhoids or rectal polyp, which are benign diseases. On histology also this variant may be confused with other more commonly occurring spindle cell lesions in this area; its recognition is therefore important as it normally has a poor prognosis.